Ocean fronts and eddies force atmospheric rivers and heavy precipitation in western North America - Xue Liu (Nature Portfolio, 2021)
Atmospheric rivers are responsible for much of the poleward water vapour transport in the mid-latitudes and can cause extreme precipitation after landfall. Here, the authors show that ocean fronts and eddies can influence atmospheric rivers and increase the associated precipitation along the North American west coast.